The Dialectic of Selective Process of NERROR Content by Youtuber Nessie Judge - Subanda, I Nyoman; Wismayanti, Kadek Wiwin Dwi; Putri, Made Narasani (Green Publisher Indonesia, 2023)
Advances in technology in the form of the internet make it easy to find information and entertainment through virtual space, one of which is YouTube. Youtube is a mass media that provides access for users to watch various videos from around the world. One type of YouTube program is the NERROR content segment. NERROR content is a video content segment created by YouTuber Nessie Judge which conveys various information on the horror genre. Aside from being a means of consuming information, this content is also popular because it provides a means for viewers to express their thoughts in the form of opinions related to the topic they are looking for. That way, researchers focus on examining how the phenomena and dialectics of the selective process of this NERROR content so that viewers choose and are interested in giving opinions. This discussion is supported by the theory of selective process media effects by using one of the concepts, namely selective exposure (media exposure). The research location is located in Denpasar and the type of research used is qualitative research supported by observational data collection techniques, in-depth interviews and documentation. The results of the study show that there are three impacts experienced by the audience after watching NERROR content, namely cognitive impact, affective impact and conative impact. Cognitive impact relates to knowledge and insight into something as seen from the audience's opinion of the content of NERROR and the audience's opinion of Nessie Judge. Then, affective impact relates to the audience's feelings regarding that seen from the audience's interest. And the last is the conative impact where this effect relates to the audience's response or action in responding to the topic of discussion of the NERROR content as seen from the results of the audience's attitude after watching NERROR content, namely the audience's personal opinion.